Decoding Adaptive Visuomotor Behavior Mediated by Non-linear Phase Coupling in Macaque Area MT - Khamechian, Mohammad Bagher; Daliri, Mohammad Reza (Frontiers in Neuroscience, 2020)
The idea that a flexible behavior relies on synchronous neural activity within intra and inter associated cortical areas has been a matter of intense research in human and animal neuroscience. The neurophysiological mechanisms underlying this behavioral correlate of the synchronous activity are still unknown. It has been suggested that the strength of neural synchrony at the level of population, is an important neural code to guide an efficient transformation of the sensory input into the behavioral action. In this study, we have examined the nonlinear synchronization between neural ensembles in area MT of macaque visual cortex by employing a nonlinear cross frequency coupling technique, namely the Bicoherence. We trained a macaque monkey to detect a brief change in the cued stimulus during visuomotor detection task. The results show that the nonlinear phase synchronization in high-gamma frequency band (100-250 Hz) predicts the animal’s reaction time. The strength of nonlinear phase synchronization is selective to the target stimulus location. In addition, the nonlinearity characteristics of neural synchronization are selectively modulated when the monkey covertly attends toward the stimulus inside the neuron’s receptive field. This additional evidence indicates that nonlinear neuronal synchronization may be affected by a cognitive function like spatial attention. Our neural and behavioral observations reflect that two crucial processes may be involved in processing of visuomotor information in area MT: (I) a nonlinear cortical process (measured by the Bicoherence), and (II) a linear process (measured by the spectral power).